(untitled) (Journal of the College of Basic Education, 2025)
The research included five chapters. The first chapter included: the importance of the research, where the researcher approached identifying the relationship between the personal traits of teachers in a boys’ football lesson and their relationship with the level of teaching competence during the lesson from the students’ perspective. The research problem was: the researcher defined the problem of his research DF through the following question (Do the personal leadership traits of football subject teachers have an impact on the lesson from the students’ perspective in the Department of Physical Education and Sports Science?) The research aimed to: prepare two questionnaires for personal traits and teaching competencies for football subject teachers from the students’ perspective and find the correlational relationship between the personal traits and teaching competencies of football subject teachers. The second chapter included: theoretical and previous studies, which included personal and leadership traits. The third chapter included the research methodology and its field procedures: the researcher used the descriptive method, the research community was determined purposively, and they are students of the second and third years of the morning study in the Department of Physical Education and Sports Science - College of Basic Education - Al-Mustansiriyah University, where their number reached (103) students distributed over the two stages (second and third), and the researcher took the community as a whole with a percentage of (100%) due to the small size of the community, and that sample was relied upon in preparing the two scales and applying them to the same sample. The fourth chapter included: presentation, analysis, and discussion after statistical processing. As for the fifth K chapter, it included the most important conclusions, which were: performing skills correctly, especially in difficult skills. Football subject teachers consider speaking elegantly with students, especially in performing new skills. The recommendations were: the necessity of using modern means used in teaching football subject, which helps to improve and develop the lesson correctly. Increasing the incentive of encouragement M and reward for students who perform the exercises correctly during the lesson.The necessity of using modern means used in teaching football subject Which helps to improve and develop the lesson correctly. Increasing the incentive of encouragement and reward for students who perform the exercises correctly during the lesson. The necessity of applying the (personal traits) scale to another sample, excluding teachers, and selecting other samples from different institutions such as the Ministry of Youth and Sports and Education